Pentosan polysulfate in patients with bladder pain syndrome/interstitial cystitis with Hunner's lesions or glomerulations: systematic review and meta-analysis. (June 2022) - Grigoryan, Bagrat; Kasyan, George; Pivazyan, Laura; Pushkar, Dmitry
Background: Bladder pain syndrome/interstitial cystitis (BPS/IC) is a persistent pain perceived in the urinary bladder region, accompanied by at least one symptom, such as pain worsening with bladder filling and daytime or nighttime urinary frequency without any proven infection or obvious pathology. The aim of this study is to evaluate the efficacy and safety of pentosan polysulfate (PPS) in patients with BPS/IC. Methods: Systematic search was performed by PRISMA checklist. Electronic databases, including PubMed and Cochrane library, were checked until 2021 using keywords: 'pentosan polysulfate', 'pain syndrome', 'interstitial cystitis', and bibliography of relevant papers was checked. Inclusion criteria: Patients with confirmed diagnosis of BPS/IC and cystoscopy criteria – Hunner's lesions. Exclusion criteria included hypersensitivity, pregnancy, lactation, and oral therapy for BPS/IC in the period of 1 month before the study and abstracts or unpublished papers. Results: In total, 13 clinical trials were included in systematic review and 7 were included in meta-analysis. Studies evaluated the effectiveness and safety of oral PPS versus placebo or other treatment options. In the first meta-analysis, three studies compared oral PPS with placebo: [relative risk (RR) = 2.07, 95% confidence interval (CI): 1.37–3.13, p = 0.0006]. The second meta-analysis of two studies compared oral PPS with another treatment options (intravesical liposome and CyA): (RR = 0.44, 95% CI: 0.10–1.93, p = 0.28). The third meta-analysis of two studies included intravesical regimen of PPS compared with intravesical placebo: (RR = 1.09, 95% CI: 0.54–2.22, p = 0.80). The majority of studies do not report any particular serious side effects. Conclusion: PPS treatment has a statistically significant effect over placebo on the subjective improvement of patients with BPS/IC. There was no difference between PPS and other treatment options. Intravesical regimen of PPS had no significant impact on response rates. None of included studies reported severe side effects after intervention.